Implications of regulatory law in conciliation: challenges from artificial intelligence and engineering for peace - Montes Alvarino, Ingrid (DIXI, 2024)
The law is not static; it evolves with the transformations of society and the regulating state. In the pursuit of controlling social risks, the legal system intervenes to the extent of legalizing social relations, giving way to regulatory law or useful law. New technologies have disrupted this networked society, driven by the advent of the internet. In this evolution, artificial intelligence has opened spaces “to manipulate knowledge as if they were human” and opens new paths and impacts for conflict resolution. Given the diversity of conflicts that citizens face in the exchange of goods and services, the State fails to resolve the high burden of social conflict, making it necessary to introduce dynamics of deregulation and delicensing, and other forms of non-state justice. Alternative conflict resolution mechanisms emerge as a response to the various crises of justice in Colombia, in the face of unsatisfied legal needs in conflict resolution and the inaction routes of Colombians. This issue is addressed to answer the objective of analyzing the implications of regulatory law in conciliation from artificial intelligence and engineering for peace. This is done from the perspectives of socio-legal research with a mixed design dimix approach to find that regulatory dynamics in the field of conciliation in law are still not strengthened, and various access barriers persist that do not guarantee access to justice, despite the intentions of Law 2220 of 2022. It is concluded that engineering for peace can be a bet for the construction of new social regulatory dynamics in conflict resolution.